EVOLUCIÓN DE LA LÍNEA I+D EN INFORMÁTICA EDUCATIVA DE LA UNIVERSIDAD EAFIT - Zea Restrepo, Claudia María; Atuesta Venegas, María del Rosario; Trujillo Vargas, John (Tecné, Episteme y Didaxis: TED, 2003)
The present article make a count of those targets, objectives, theories and projects that have given continued life to the group of Research and lnvestigation in Educative Computer Aplication at the University Eafit, and how its management and projection have stayed within the scheme of promotion of significant approaches of the technology to the learning environments.